2011
DOI: 10.1177/0022002711422340
|View full text |Cite
|
Sign up to set email alerts
|

When War Hits Home

Abstract: The ''proximate casualties'' hypothesis holds that popular support for American wars is undermined more by the deaths of American personnel from nearby areas than by the deaths of those from far away. However, no previous research has tested the mechanisms that might produce this effect. This omission contributes to three areas of lingering uncertainty within the war support literature: whether national or local losses have a greater effect on war support, whether the negative effects of war deaths are durable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…One methodological challenge of studying the willingness to fight is the validity of respondents’ answers. People may behave differently from their responses in surveys, and they may also change their attitude toward participation if war becomes a reality (Althaus, Bramlett & Gimpel, 2012). However, recent studies find a strong correlation between survey responses and real-world behaviors on contested issues (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…One methodological challenge of studying the willingness to fight is the validity of respondents’ answers. People may behave differently from their responses in surveys, and they may also change their attitude toward participation if war becomes a reality (Althaus, Bramlett & Gimpel, 2012). However, recent studies find a strong correlation between survey responses and real-world behaviors on contested issues (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Public opinion, however, mainly reacts to local-rather than national-casualties (Gartner et al, 1997;Shen, 2012, 2014). Furthermore, the effect of casualties decays rapidly, and is strongest in individuals who are less attentive to national and local news-where a possible explanation is that such individuals are more likely to experience the casualties information in a more personal way (Althaus et al, 2012). Most illustrative is the finding that while the events of 9/11 lead to public support for president Bush and enabled the war in Iraq, personal ties to 9/11 casualties were negatively correlated with presidential support (Gartner, 2008b).…”
Section: Mobilization In Intergroup Conflictmentioning
confidence: 99%
“…Past research has measured social proximity to the military through both social and geographic proximity including having a relative who served (Gartner 2008), the nearby veteran population density (Krueger and Pedraza 2015), and local casualties (Althaus, Bramlett, and Gimpel 2012). They have found that proximity to a group is associated with stronger support for the group on salient issues (Krueger and Pedraza 2015) or on the increased importance of the group’s considerations when reaching a decision (Lau, Brown, and Sears 1978).…”
Section: Military Intervention Attitudes and Social Attachmentsmentioning
confidence: 99%